Penegakan Hukum Pidana terhadap Pelaku Tindak Pidana Penadahan di Kepolisian Resor Tanjung Jabung Barat - Nurhasan Nurhasan (Universitas Batanghari Jambi, 2023)
The act of collecting will lead to other criminal acts, because the perpetrators of collection dare to buy or exchange, hold or mortgage property obtained as a result of crime. For this object is seen by other criminals as a market for the sale or other goods resulting from the crime committed. The approach method used is sociolegal research with empirical juridical research and data sources come from library research and field research, sampling techniques by means of Purpose sampling and data collection techniques by means of interviews and then qualitative analysis is carried out. The result is that law enforcement against the perpetrators of criminal acts of collection has not been optimally carried out in accordance with the provisions/procedures of law enforcement officers at the police level. Because it involves actors with well-organized networks and the obstacles faced in enforcing the law against perpetrators of the crime of receiving are the difficulty in finding and identifying crime points. Collection is done because it has a hidden or hidden network and cooperates very well so it is difficult to detect and trace.